Origin and Structure of Political Parties in a Communist State and in a Capitalist Country and their Evolution VIZ-A-VIZ., Islamic Political Parties - Taimoor Kamal Malik (Policy Journal of Social Science Review, 2026)
The annals of political theory are silent with reference to creation of the concept of the political party; though the writers have tried to link this phenomenon with the Middle Ages of the Europe and then in the composition and constitution of USA. But there has always been a need to philosophically try and find its genesis. The very idea of a political party and its evolution have always been a topic of interest with the political thinkers. The present paper is an attempt in this regard not only to trace the origin of the idea of political parties but the Paper throws light on an idea that Plato in his The Republic has been the first one who floated the idea of a Political Party. Though, it might be unintentional, unwitting and perhaps unconscious but his idea of a city-state is the same as it is of a modern-day political party structure with a bit modification and up-dation. This paper analyses the concept of a political party, its evolution and the approved mechanism of its operation. Then through diagrammatic illustration, it lays bare the structure of an American political party, mode of recruitment and its inherent structure. Then this Paper elaborates the Chines Communist party structure and draws parallel of political party of a capitalist country with that of a communist state. Then, there has been an attempt to put a comparative chart which is combined and named as TK-Comparative Chart, where it is tried to put across that Platonic idea of a city-state is actually a prototype of a modern-day political party structure and there are amazingly similarities on every account of a political party whether it is communist or capitalist. Then this paper also dwells upon Islamic concept of political party as there is no such defined concept as it is a divinely ordained religion where there is no concept or room for eternal disagreement or a separate political manifesto other than the one revealed and preached through the Holy Quran.